Assessment of the Technical Condition of the Kossak Manor Granary Building in Górki Wielkie - Juraszek, Janusz; Siry, Roman; Walusiak, Hubert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents an assessment of the technical condition of the Manor Granary Barn of Zofia Kossak in Górki Wielkie. Due to its architectural value, the building holds special significance for the local community. Proper verification of the technical condition was crucial for the planned renovation and reconstruction in the next stage. It is planned that the Granary building will be transformed into an office and service complex with gastronomic and cultural elements as part of the "Kossak Educational and Cultural Center" project in the future.
Keywords: granary; historic building; renovation; reconstruction